Growth assessment of children during the COVID‐19 pandemic—Can we rely on parental measurements?. (27th July 2021) - Tenenbaum, Ariel; Shefer‐Averbuch, Noa; Lazar, Liora; Yakobovitch‐Gavan, Michal; Phillip, Moshe; Oron, Tal
Abstract: Aim: The COVID‐19 pandemic prompted the rapid development of remote medical services. During lockdown periods, children's growth data were obtained from parents' home assessments. This study aimed to assess the accuracy of home height and weight measurements and analyse their utility in clinical decision‐making. Methods: A retrospective, single‐centre observational study. Children aged 3–18 years were measured for weight and height at home using guidance provided to parents on proper measurements techniques before subsequent professional re‐evaluation at our endocrine institution clinic. The two sets of measurements were compared and analysed according to various clinical parameters. Results: Height measurements at home and in the clinic were comparable (diff = 0.1 ± 1.3cm, p = 0.42) amongst the 107 children (mean age 10.2 ± 3.7, 56.1% males) participating in the study, except in overweight and obese children where they were significantly higher in the clinic (diff = 0.86 ± 1.48cm, p = 0.018). Weight and BMI were significantly higher in the clinic (diff = 0.45 ± 0.8kg and diff = 0.3 ± 0.6kg/m 2, p <0.001 and p <0.001, respectively). Conclusions: Height measurements of children by their parents were accurate except in obese and overweight children, whereas weight measurements tended to be lower than in the clinic. With proper guidance, parents' home measurements of height and weight are accurate and suitable for clinical decision‐making.